Techno-commercial resource assessment of ocean wave energy in the Philippines - Quitoras, Marvin Rhey D. (College of Engineering, University of the Philippines Diliman, 2016)
Philippines is currently addressing its growing concerns on how to meet its ballooning energy demand in parallel on having a good energy mix in terms of its renewable and non-renewable resources.As of 2014,according to U.S. Energy Information Administration, roughly 60% of the Philippines' sources of energy came from the non-renewables and the remaining percent was mainly attributable to the renewables such as hydro,geothermal,biomass,etc.Interestingly,at the moment, ocean energy is still not part of the current energy mix.The main focus of the study is to see the potential of ocean energy,particularly commercial and technical perspective of project development.More so,this work intends to point out and quantify the wave resources of the country specifically located in 47 points scattered in Catanduanes,Eastern Samar, Western Luzon,Siargao Island and Surigao Del Sur.Such map can improve the current ocean wave resource map developed by the Department of Energy(DOE).There are lots of technologies to be used in harnessing the wave energy.However,at this particular research,three Wave Energy Converters(WECs)such as AquaBuoy,Pelamis and Wave Dragon are considered with respect to their advance Technology Readiness Levels(TRL).Moreover,all data such as wave height and period which are needed for estimating the wave potential of a certain area came from a certain surf-forecast website.Such data was captured on a regular basis until coming up with a one year historical wave data on a 3-hour interval per day.This study also proposes the use of a model that will forecast the viability of ocean wave projects,both in a technical and commercial perspective.The model must be robust and replicable which can be used on a local and in an international setting for the benefit of all the stakeholders.